A proposta de educação do MST e o PPP do CEIAS: uma análise descritiva de suas convergências e divergências (1996-2012) - Ferreira Sobrinho, José (2014)
To contextualize the topic and research problem, in the Brazilian context, we emphasize the quantity and complexity of connections that allow us to understand the field of education as a concrete phenomenon (synthesis of many determinations). Therefore, within this larger context, we present a space-time frame for explicitarmos the field context in Paraná from the late 1990s and inserting the Rural Education as a theoretical element and study of our research object. Based on the above, the research problem in question is to analyze how the Proposal of the State Sector of the MST Education materializes or not in the State College Field Ireno Alves dos Santos (1999-2012), Rio Bonito do Iguaçu, State Paraná. Therefore, the steps in the way of research as instruments to achieve the proposed specific objectives are defined as follows: identify how it is organized and how it works pedagogically the school researched field; to compare the resolutions of the State Sector of the MST Education front of the Pedagogical Political Project of the State College Field Ireno Alves dos Santos; and analyze which design education guides each of these pedagogical practices. Thus, we first analyze based on literature the agrarian question in Brazil, to then look at the context of the field in Paraná from the late 1990s and understand how the MST is inserted in this context as wielding flags the struggle for Agrarian Reform and Education - understanding that in practice both are inseparable. From here we will also review based on field research how this scenario of struggle gives way to training camp history "Hole" to the margins of that in years gone 90 (1996) was still called PR, currently BR 158 (federal highway). There begins a long process of struggle and resistance culminating in the occupation of one of the largest estates in southern Brazil and the creation of Ireno settlement Alves dos Santos, in which a state college field, namesake, located in Arapongas community is the site of our research.